What every BODY is saying : an ex-FBI agent's guide to speed-reading people - Navarro, Joe, 1953- (Collins Living, 2008)
Read this book and send your nonverbal intelligence soaring. Joe Navarro, a former FBI counterintelligence officer and a recognized expert on nonverbal behavior, explains how to "speed-read" people: decode sentiments and behaviors, avoid hidden pitfalls, and look for deceptive behaviors. You'll also learn how your body language can influence what your boss, family, friends, and strangers think of you.